The Impact of Digital Payment Adoption on Financial Accuracy and Accounting Efficiency in Small and Medium Enterprises - Erwan Aristyanto; Ratna Tri Hardaningtyas; Akhatova Shakhnoza Akram kizi (International Forum of Researchers and Lecturers, 2024)
This study explores the impact of digital payment adoption on financial accuracy and efficiency within Small and Medium Enterprises (SMEs). The rapid shift towards digital financial tools has reshaped accounting practices in SMEs, offering both opportunities and challenges. Traditional cash-based accounting systems have long been prone to errors due to manual processes and human intervention, which hinder the reliability and accuracy of financial records. Digital payment systems, including mobile payments, online bank transfers, and e-wallets, provide a solution by automating financial transactions, thus reducing human error and enhancing operational efficiency. The research involved a quantitative survey of 120 SME owners, analyzing the relationship between digital payment adoption and improvements in accounting accuracy and efficiency. The findings revealed that SMEs implementing digital payment systems saw a 28% improvement in accounting accuracy, accompanied by a substantial reduction in transaction errors. Additionally, the use of digital tools was associated with improved accounting efficiency, including faster transaction processing times and a decrease in time spent on routine financial tasks. This study highlights the effectiveness of digital payment systems in streamlining accounting operations and ensuring more accurate financial reporting, which is essential for informed decision-making and stakeholder trust. However, challenges such as technological constraints, resistance to change, and a lack of digital literacy among SME owners and employees remain barriers to widespread adoption. To address these issues, SMEs should invest in employee training, enhance digital infrastructure, and foster a culture of innovation. Governments and institutions can play a crucial role by offering financial incentives, improving digital infrastructure, and providing support through digital literacy programs. These efforts will facilitate the transition to digital payment systems and contribute to the long-term sustainability and competitiveness of SMEs.